Florence Nightingale and the historical, social and cultural context of her time - Alica Hanzeliková Pogranyivá; María José Carabaño Mariblanca; Beatriz Torresano Torresano; María Rosario García Moreno (Universidad de Alicante, 2012)
This paper aims to review the life of the founder of professional nursing and the historical, social and cultural context in which it developed. Florence Nightingale, the first nursing theorist, applied her knowledge of history and philosophy to the study of reality, by focusing on what became the centre of her life: people's health care. To understand her life it is necessary to remember the situation of a country that had just started the deep transformation of the social relations of production and distribution of material and spiritual goods. As a consequence of the Industrial Revolution, a new social class appeared, the bourgeoisie, transforming not only material standards of living but also thought. Catholic dogmatism turned into religious reform, giving way, in regards to England, to the establishment of Anglicanism as the official religion and to other Protestant currents.